Check list of the Venezuelan millipedes species - Bueno-Villegas, Julián; Sierwald, Petra; de Ascenção, Antonio A. (Zootaxa, 2019)
Here we provide a checklist of millipedes described or recorded in the literature from Venezuela. The diplopod fauna is comprised of eight orders, 18 families, 54 genera, and 157 species. The millipede orders Glomerida, Chordeumatida, Julida, Siphoniulida, and Platydesmida (known elsewhere in the Western Hemisphere) are not, as of yet, reported from the Venezuelan fauna. Two widely distributed invasive species, Asiomorpha coarctata and Oxidus gracilis, were recorded from Venezuela. All species records listed here contain comprehensive citation and synonymy lists. Numerous locality data are questionable and are discussed. For most species, the supposed deposition of the type specimens is given. However, the museum and gender information is taken mostly from the literature as the type specimen themselves were not examined. An analysis of records extracted from GBIF in 2016 and in 2018 was conducted and compared to the data captured from the published taxonomic literature. The data in this checklist are summarized online at the MilliBase website.